The Effect of Emergency Level and Response Time on Patients' Length of Stay in the Emergency Room of Muhammadiyah Hospital Kediri - Baiq Yuliatri Kusumardani; Siti Farida Noor Layla; Yenny Puspitasari (Journal Of Nursing Practice, 2024)
Background: Emergency services are medical actions needed by emergency patients. Overcrowding in the Emergency Room that happen with increasing number of patient which has an impact on length of stay and lead to patient dissatisfaction. Purpose: The aim of research was to analyze the effect of emergency level and response time on length of stay in the emergency room of Muhammadiyah Hospital Kediri. Method: The research design uses analytic observational with a cross sectional approach. The independent variables are level of emergency and response time. The dependent variable is Length of Stay. The population was all patients in the ER of Muhammadiyah Kediri Hospital at August - October 2022 as much  as 142 patients. Samples taked used Simple random sampling technique as many as 105 respondents. Data collected used observation sheets and analyzed with multiple linear regression. Results: The results showed that partially and simultaneously of independent variables (Emergency Level and Response time) had a p-value less than 0.05 so that affected the length of stay. Conclusion: The results showed that emergencies level of patients caused experience a worsening of their condition or it will get worse if there are complications in patient's if they are not treated immediately, in addition to that, the officers respond quickly in services in the emergency room from the time patient arrives until treated will affect length of stay in the emergency room. This showed that’s there is an influenced of Emergency Level and Response Time on the Length of Patient's Stay.